Simple and Low Cost Design of Infusion Device Analyzer Based on Arduino - Jannah, Nikmatul; Syaifudin, Syaifudin; Soetjiatie, Liliek; Ali, Muhammad Irfan (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2020)
In the medical world, patient safety is a top priority. The number of workloads and frequency of use in the long term will affect the accuracy and precision of the equipment. Therefore calibration is needed, namely the measurement activities to determine the truth of the appointment value of measuring instruments and measuring materials based on the standards of the Minister of Health Regulation No. 54/2015. The purpose of this study is to design an infusion device analyzer to measure the flowrate parameter using the Arduino microcontroller. The main advantage of this study is that the system can display three calibration results in one measurement at the same setting. The results of the calibration will determine the feasibility of an infusion pump or a syringe pump. This study uses the flow rate formula, which is applied to the water level system to obtain the calibration results. The infrared photodiode sensor will detect the flow of water in the chamber that comes from the infusion or syringe pump. Furthermore, the sensor output will be processed by the microcontroller, and the reading results are displayed on the liquid crystal display. The average measurement at a setting of 10 ml/hour is 9.36 ml/hour, at a setting of 50 ml/hour is 46.64 ml/hour, and at a setting of 100 ml/hour is 96.04 ml/hour. Based on available data, this tool has an average error value of 5.69%, where the value exceeds the tolerance limit allowed by ECRI, which is ± 5%